White Working-Class Voices Multiculturalism, Community-Building and Change - Beider, Harris (2015)
Popular views of white working-class communities are common but knowledge of their views on multiculturalism and change less so. This important book provides the first substantial analysis of white working-class perspectives on themes of multiculturalism and change in the UK, creating an opportunity for these 'silent voices' to be heard. Based on over 200 interviews in multiple sites the results are startling - challenging politicians, policy makers and researchers. Improving our understanding of how this group went from 'hero to zero', became framed as racist, resistant to change and disconnected from politics, the book suggests a new and progressive agenda for white working class communities to become a fully inclusive part of a modern and diverse country in the 21st century. The book will be valuable to academics and students as well as policy-makers and practitioners in national government and organisations.